ANALISIS EMOTIONAL INTELLIGENCE, EFIKASI DIRI DAN PERUBAHAN ORGANISASI TERHADAP KINERJA MELALUI MOTIVASI PADA PT ANGKASA PURA I (PERSERO) - Dewi Andriani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2021)
PT Angkasa Pura I must carry out restructuring (rearrangement) and reform in the hope of sustainable change. Proper management of employees will create high employee performance which in turn will encourage increased performance. However, PT Angkasa Pura I is facing problems in decreasing the quality and quantity of work results from the specified work standards. Many factors affect employee performance including emotional intelligence, self-efficacy and organizational change. The population in this study were all employees of the Non-Crew Operations Unit of PT Angkasa Pura I, with a total sample of 80 people. The analytical technique used is PLS analysis.Based on the results of the analysis and hypothesis testing that have been carried out and the objectives to be achieved from the research, the following conclusions can be obtained: The results of the analysis obtained that Emotional Intelligence has no contribution to motivation. Self efficacy has no contribution to motivation. Organizational change has a contribution to motivation. Emotional Intelligence has no contribution to performance. The results of the analysis obtained that self-efficacy does not have a contribution to performance. Organizational change has a contribution to performance. The results of the analysis obtained that motivation has a contribution to performance, and the variable Organizational Change provides the largest indirect effect on performance through motivation. This shows that organizational change will increase when through motivation.